Early Versus Standard Antiretroviral Therapy for HIV Infected Adults in Haiti - Severe, Patrice (2010)
BACKGROUND: The optimal time to start antiretroviral therapy (ART) for HIV–infected adults in resource limited settings with a CD4(+) T cell count of 200 – 350 cells per mm(3) remains uncertain. METHODS: We conducted a randomized, open label, trial of early versus standard ART initiation in HIV-infected adults with no history of an AIDS illness and a confirmed CD4(+) T cell count between 200 and 350 cells per mm(3) in Haiti. The primary study end point was survival. Participants in both groups received monthly follow up, isoniazid and trimethoprim-sulfamethoxazole prophylaxis, and nutritional support. The early treatment group initiated zidovudine, lamivudine, and efavirenz within two weeks of enrollment. The standard group started the same ART regimen when participants developed a CD4(+) T cell count ≤ 200 cells/mm(3) or clinical AIDS. RESULTS: Between 2005 and 2008, 816 participants, 408 per group, were enrolled and followed for a median of 21 months. The CD4 T cell count at enrollment was ~ 280 cells per mm(3) in both groups. There were 23 deaths in the standard group and 6 in the early group, p=0.0011, hazards ratio 4.0, 95% CI 1.6 to 9.8. There were 36 incident tuberculosis cases in the standard group and 18 in the early group, p = 0.0125, hazard ratio 2.0, 95% CI 1.2 to 3.6. CONCLUSIONS: Early ART decreased mortality and incident tuberculosis infection. Access to ART should be expanded to all HIV–infected adults with a CD4(+) T cell count < 350 cells per mm(3), including those from resource limited settings.